(untitled) (Research, Society and Development, 2021)
The research sought to verify the feasibility of the use of civil construction waste as a contributor to the physical and mechanical characteristics of self-compacting concrete. Four treatments were tested facing the performance of the reference trait. Mixtures with replacement of 35, 40 and 45% of the fine aggregate by concrete residue to workability. The amount of additive was experimentally determined by testing in the fresh state. The treatments were submitted to evaluation of segregation endurance, passing ability, workability, absorption, compressive strength, and modulus of elasticity. With the obtained results in the fresh state, it is possible to infer that the mixes with the addition of residue maintained the characteristics of self-compacting concrete, being possible to classify its use according to the results required by the standard. For the tests in hardened form, the mixes with the addition of 35% and 45% of concrete residue achieved lower strengths than the reference mix by 17% and 24% respectively, only the mix with 40% addition exceeded the reference mix, at 56 days.